Identifikasi Ikan Lokal di Aliran Sungai Brantas Desa Curungrejo Kabupaten Malang - Muawanah Muawanah; Dayang Diah F; Anjas Sasana Bahri; Muhammad Kholil Mufadol (Journal on Education, 2021)
This research was conducted in the Brantas River, Curungrejo Village, Kepanjen District, Malang Regency. The purpose of this study was to identify the presence of local fish in the Brantas River, Curungrejo Village, Malang Regency. The method used in this study is descriptive method with data collection including primary data and secondary data. Data collection was carried out by means of active participation, observation, interviews, documentation and literature study. The results obtained from this research are that there are various types of fish in the waters of the Brantas River, Curungrejo Village, Kepanjen District. There were 5 species of fish caught during the study, namely Tawes Fish (Barbonymus gonionotus), Wader Pari Fish (Rasbora argyrotae), Snakehead Fish (Channa striata), Mujair Fish (Oreochromis mossambicus) and Catfish (Clarias gariepinus). The most dominant species in the waters of the Brantas River is the Pari Wader Fish (Rasbora argyrotae) with a total catch during the study of 25 fish. The conclusion obtained in this study is that the most dominant species in the waters of the Brantas River is Wader Pari fish (Rasbora argyrotae) with a total catch during the study of 25 fish.